LITERASI KESEHATAN: MENGENAL LEBIH DEKAT TENTANG PENCEGAHAN DAN PENANGANAN GASTRITIS PADA MAHASISWA STKIP HAMZAR - Maruli Taufandas Maruli; Apriani Susmita Sari; Hikmah Lia Basuni; Muh. Jumaidi Sapwal; Ririnnisahawaitun Ririnnisahawaitun; Ahyar Rosidi; Anatun Aupia (Jurnal Pengabdian Masyarakat Kesosi, 2023)
The condition that is often experienced by students is gastritis. Gastritis is one of the disorders of the digestive system that occurs due to an imbalance of stomach acid; gastritis often occurs if the diet is irregular, such as in students who have to go to college every morning. Some students sometimes don't have time to have breakfast which causes a person to experience stomach ache or gastritis. Gastritis can be a serious problem for students/adolescents, be it acute gastritis or chronic gastritis that students can experience. One of the causes of gastritis is a poor diet, not having breakfast before going to college. To minimize gastric disturbances or gastritis, of course, the role of health workers is required to provide health education or health literacy so that students understand what must be done to prevent gastritis. The purpose of this PKM is to prevent and minimize the occurrence of gastritis in students/adolescents. The method used in this service is in the form of health education or health counseling aimed at students, how to measure the level of understanding of the material provided is then carried out pretest and posttest. The results of community service in the form of an increase in the level of student knowledge about gastritis were strengthened by the results of the Wilcoxon test p value 0.001, p value <0.05, there was an effect of health literacy about gastritis on the level of student knowledge about gastritis.